Uji Penggunaan Pupuk Kandang Kambing Terhadap Pertumbuhan Dan Hasil Tanaman Kemangi (Ocimum Sanctum L.) - M Abror (Savana Cendana, 2023)
This study aims to determine the effect of the use of goat manure on the growth and yield of basil plants. This research was carried out on campus land, Modong Village, Tulangan District, Sidoarjo Regency from December 2022 to February 20223. This study used a Group Randomized Design (RAK) with a single fak tor, namely fermented goat shrimp solid fertilizer consisting of 7 treatments, namely: 10 tons / ha, 12.5 tons / ha, 15 tons / ha, 17.5 tons / ha, 20 tons / ha, 22.5 tons / h a , 25 tons / ha. Data analysis uses variant analysis (Anova) and if there is a difference, further tests of Honest Real Difference (BNJ) 5% and 1% are carried out. From the observations, the results showed a real effect on the observation of plant height aged 7 HST in P7 treatment and crop index measurement in P4 treatment and also had a very real effect on measuring the wet weight of plants in P3 treatment.